Prediction of critical heat flux under non-uniform heating in a 3 × 3 rod bundle based on CMFD - Fu Shengwei; Jiang Jiacheng; Jiang Jiahang; Jiao Meng (Annals of Nuclear Energy, 2026)

Alkali-triggered kinetic matching of polymerization and crosslinking enables hydrogels with programmable mechanics, flexible sensing, and dynamic information encryption - Hongyan Cao; Shengwei Fu; Yaqing Ge; Xueting Yang; Xiaoli Wang; Xianglei Zhao; Yanyan Zhao; Xiangling Gu (Chemical Engineering Journal, 2026)

An interpretable multi-task learning model for effluent quality and greenhouse gas emissions prediction in wastewater treatment plants - Chenyue Sun; Shengwei Pei; Raziyeh Farmani; David Butler; Guangtao Fu (Water Research, 2026)

Shifts in the Upper Limit of Alpine Grasslands Lag Behind Climate Warming Across the Tibetan Plateau - Licong Liu; Kai Zhu; Jin Chen; Miaogen Shen; Xuehong Chen; Ruyin Cao; Wei Yang; Eryuan Liang; Tianxiang Luo; Peng Hou; Shengwei Zong; Mingkai Jiang; et al. (Global Change Biology, 2026)
Alpine grasslands are vital for biodiversity and ecosystem service delivery, yet their responses to climate change remain a focus of intense scientific interest. While studies have examined separate ecological processes such as biodiversity changes or treeline shifts, broader ecosystem changes are not as well understood. Here, leveraging time series of high‐resolution images from the Landsat satellite, we developed an automated method to track the shifts in the upper limits of alpine grasslands on the high and expansive Tibetan Plateau, a region of high ecological and climatic significance. Our analysis revealed modest upward boundary shifts of −0.55 to 0.99 m year −1 (2nd–98th percentile; mean = 0.12 m year −1 ) across the plateau over nearly four decades, from 1986 to 2023, with faster rates in wetter areas, yet drastically slower than the rapid climate‐driven isotherm shifts of 3.35 to 12.04 m year −1 . This substantial lag, further confirmed by ≤ 3 m resolution satellite images, is potentially attributed to water scarcity, poor soil quality, and a lack of stable substrates beyond the current boundaries and geomorphological features. Consequently, the upward expansion of alpine grasslands on the Tibetan Plateau—attributed to the shift of the upper grassland boundary—was limited to approximately 6100 km 2 . Notably, two high‐spatial‐resolution CMIP6 models simulated more rapid upward expansion of alpine grasslands and greater carbon sequestration than observed. These findings underscore the need to integrate local environmental nuances into future predictions. Our study elucidates the resilient yet vulnerable nature of alpine ecosystems, sparking new conversations regarding effective strategies to safeguard these extraordinary landscapes under changing climate.

Enhanced LSHADE-SPACMA with fitness-directed selection pressure mutation and elastic archive for UAV trajectory planning and PV parameter identification - Wenhao Mao; Shengwei Fu; Guozhang Zhang; Haisong Huang; Guangming Gong; Yulu Liu; Honghai Fu; Yinwei Li; Yongpeng Zhao; Langlang Zhang; Jiawei Wang (Swarm and Evolutionary Computation, 2026)

Effects of flow-guiding block on water transport and performance in modified PEMFC gas flow channel - Lirong Fu; Baoshuo Yu; Shengwei Wu; Jinyi Liu; Huadong Lin; Na Qiu (Fuel, 2025)

Reduced Usage of GLS Intronic Polyadenylation Promotes Cellular Senescence - Xueping Li; Yuxin Li; Dong Ding; Baiyun Xie; Jun Yao; Yu Chen; Zhaozhao Zhao; Peng Yu; Shengwei Zhang; Fu Yang; Ting Ni; Gang Wei (Phenomics, 2025)

Robustness of neuro-evolution in urban drainage system control under communication failures: comparing centralized and decentralized control schemes - Shengwei Pei; Guangtao Fu; Lan Hoang; David Butler (Water Research, 2025)

Real-time multi-objective optimization of pump scheduling in water distribution networks using neuro-evolution - Shengwei Pei; Lan Hoang; Guangtao Fu; David Butler (Journal of Water Process Engineering, 2024)

Numerical simulation of improving the dispersion and migration characteristics of tiger nut tuber-soil mixture with a novel variable-amplitude flexible screen - Shengwei Zhang; Hongfang Yuan; Qingqiu Cao; Yan Zhang; Jun Fu; Xiangyu Wen (Computers and Electronics in Agriculture, 2024)

Real-time control of urban drainage systems using neuro-evolution - Shengwei Pei; Lan Hoang; Guangtao Fu; David Butler (Journal of Environmental Management, 2024)

Wide bandgap polymer donors with an acceptor1-π-acceptor2-π configuration for efficient polymer solar cells - Qisheng Tu; Yunlong Ma; Shengwei Shen; Dongdong Cai; Jin-Yun Wang; Huiting Fu; Qingdong Zheng (Chemical Engineering Journal, 2024)

Improving in-stream nutrient retention potential through factitious manipulation: the stepping stone structures of flying-geese pattern and their reinforcement structures - Shengwei Xu; Ruzhong Li; Yang Fu (Environmental Science and Pollution Research, 2023)

Identifying nonlinear interactions between PM2.5 and O3 on small time scales with visibility graph approaches - Shengwei Liu; Zuntao Fu (Atmospheric Pollution Research, 2023)

A calibration method for contact parameters of agricultural particle mixtures inspired by the Brazil nut effect (BNE): The case of tiger nut tuber-stem-soil mixture - Shengwei Zhang; Ruiyu Zhang; Qingqiu Cao; Yan Zhang; Jun Fu; Xiangyu Wen; Hongfang Yuan (Computers and Electronics in Agriculture, 2023)

Research on effects of rolling motion on a pressurizer surge line based on the fluid-solid-thermal coupling method - Hang Yu; Xinwen Zhao; Shengwei Fu; Kang Zhu (Annals of Nuclear Energy, 2023)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)